The financial crisis and sizable international reserves depletion: From "fear of floating" to the "fear of losing international reserves"? - Joshua Aizenman; Yi Sun (University of California, Santa Cruz Institute for International Economics (SCIIE), 2009)
This paper studies the degree to which Emerging Markets (EMs) adjusted to the global liquidity crisis by drawing down their international reserves (IR). Overall, we find a mixed and complex picture. Intriguingly, only about half of the EMs relied on depleting their international reserves as part of the adjustment mechanism. To gain further insight, we compare the pre-crisis demand for IR/GDP of countries that experienced sizable depletion of their IR, to that of courtiers that didn't, and find different patterns between the two groups. Trade related factors (trade openness, primary goods export ratio, especially large oil export) seem to be much more significant in accounting for the pre-crisis IR/GDP level of countries that experienced a sizable depletion of their IR in the first phase of the crisis. These findings suggest that countries that internalized their large exposure to trade shocks before the crisis, used their IR as a buffer stock in the first phase of the crisis. Their reserves loses followed an inverted logistical curve - after a rapid initial depletion of reverses, they reached within 7 months a markedly declining rate of IR depletion, losing not more than one-third of their pre crisis IR. In contrast, for countries that refrained from a sizable depletion of their IR during the first crisis phase, financial factors account more than trade factors in explaining their initial level of IR/GDP. Our results indicate that the adjustment of Emerging Markets was constrained more by their fear of losing international reserves than by their fear of floating.
Keywords: F15; F21; F32; F43; 330; trade shocks; deleveraging; international reserves; emerging markets; Finanzmarktkrise; Währungsreserven; Buffer-Stock-Ansatz; Aufstrebende Märkte